Platform Keibubapaan Digital (Platform KID) : market validation report - Mohamed, Shafizan; Yusoh, Mohd Helmi; Mohd Nasir, Nur Shakira; Wan Mohd Ghazali, Wan Norshira; Janon, Nazariah Shar'ie; Salleh, Norsaremah (Communication and Media Centre AbdulHamid AbuSulayman Kulliyyah of Islamic Revealed Knowledge and Human Sciences, 2025)
This report presents the findings of a market validation study conducted to assess the viability, relevance, and direction of Platform KID. Supported by the Ministry of Science, Technology and Innovation (MOSTI), this study is the result of a collaborative research effort that integrates empirical evidence, parental voices, and community insights to better understand the digital parenting landscape in Malaysia.